The Influence of Leadership, Physical Work Environment and Discipline on Employee Performance at PT. BPR Mambal Abiansemal - Ni Luh Putu Nila VERDIANTI; Ni Made RUSTINI; A.A. Istri Krisna Gangga DEWI (Loka: Journal Of Environmental Sciences, 2023)
Purpose:This research examines and analyzes the influence of leadership, physical work environment, and work discipline on employee performance.Methodology:This research was conducted at PT. BPR Mambal, in Abiansemal, Badung, Bali, used saturated sampling techniques to collect a research sample of 36 respondents. The data obtained from the distribution of the questionnaire is suitable for use. The data was then analyzed using multiple linear regression and hypothesis testing (t-test and f-test).Findings:The research results showed that (1) it was found that leadership, the physical work environment and work discipline had a significant effect on employee performance, and (2) it was obtained that leadership had a positive and significant effect on employee performance. It means that the better the leadership is, the more employee performance at PT will increase. BPR Mambal, in Abiansemal, Badung, Bali. (3) it was found that the physical work environment positively and significantly affected employee performance. It means that the better the physical work environment, the greater the employee performance at PT. BPR Mambal, in Abiansemal, Badung, Bali (4), found that work discipline positively and significantly affects employee performance.Implication:It means that the more work discipline increases, the more employee performance at PT will increase. BPR Mambal, in Abiansemal, Badung, Bali.